2020
DOI: 10.3892/ijmm.2020.4791
|View full text |Cite
|
Sign up to set email alerts
|

YAP and Wnt3a independently promote AECIIs proliferation and differentiation by increasing nuclear β‑catenin expression in experimental bronchopulmonary dysplasia

Abstract: Arrested alveolar development is the main pathological characteristic of neonatal bronchopulmonary dysplasia (BPD); however, a number of studies aiming to improve alveolarization have focused on alveolar epithelial cell damage and impairment. Previously, the authors reported that the Wnt signaling plays a key role in alveolar injury and repair by regulating alveolar epithelial type II cell (AECII) proliferation and differentiation. In the present study, the authors wished to investigate whether Yes-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The respiratory epithelial cells of mature lung are stationary under normal physiological conditions, but a variety of epithelial cells, such as type II alveolar epithelial cells (AECIIs) and basal cells, significantly regenerate when lung is injured [ 58 60 ]. It is reported that the YAP improves the self-renewal of AECIIs and the differentiation of AECIIs into type I alveolar epithelial cells (AECIs) with lung injury [ 59 , 61 , 62 ]. In addition, YAP is essential for AECIIs proliferating or differentiating into AECIs in response to mechanical tension [ 59 , 61 , 63 , 64 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The respiratory epithelial cells of mature lung are stationary under normal physiological conditions, but a variety of epithelial cells, such as type II alveolar epithelial cells (AECIIs) and basal cells, significantly regenerate when lung is injured [ 58 60 ]. It is reported that the YAP improves the self-renewal of AECIIs and the differentiation of AECIIs into type I alveolar epithelial cells (AECIs) with lung injury [ 59 , 61 , 62 ]. In addition, YAP is essential for AECIIs proliferating or differentiating into AECIs in response to mechanical tension [ 59 , 61 , 63 , 64 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
“…It is reported that the YAP improves the self-renewal of AECIIs and the differentiation of AECIIs into type I alveolar epithelial cells (AECIs) with lung injury [ 59 , 61 , 62 ]. In addition, YAP is essential for AECIIs proliferating or differentiating into AECIs in response to mechanical tension [ 59 , 61 , 63 , 64 ]. In the process of alveolar regeneration, AECIIs responds to the increase of mechanical forces outside the environment, which lead to the aggregation and the activation of YAP in nucleus and promote the proliferation of AECIIs as well as the differentiation of the AECIIs into AECIs [ 59 , 61 , 63 , 64 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wnt protein activation, intra-cellular and extra-cellular transportation, and binding to cell surface receptors are dependent on MUFA residues. In previous studies, the critical role of Wnt3a, as the main member of the Wnt family, has been documented in the niche of stem cells [ 11 13 ]. Like other members of the Wnt cascade, Wnt3a can transfer signaling to downstream effectors, such as the β-catenin/canonical pathway after MUFA-mediated interaction with cell surface receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In newborn lung tissue, Wnt/βcatenin signaling pathway affects lung cell differentiation and lung tissue structure, and is abnormal activation in the lungs of rats with pulmonary fibrosis [10]. Wnt/β-catenin pathway was activated in lung tissue in animal models of BPD and idiopathic pulmonary fibrosis, which suggested that Wnt/β-catenin pathway had potential as a therapeutic target for the treatment and prevention of BPD [11,12].…”
Section: Introductionmentioning
confidence: 99%